A Schnittke reader - Schnittke, Alfred, 1934-1998 (Russian music studies (Bloomington, Ind.), 2002)
"The compositions of Alfred Schnittke are known for their exquisite construction, their unlikely embrace of material from disparate sources, their predisposition for melancholia, and their tremendous beauty. But Schnittke was also a prolific writer on a wide variety of subjects. This compilation, the first English-language collection of Schnittke's writings, is one of the composer's last works. Included, are previously published and never before-published essays on his own compositions; on other composers and performers such as Dmitri Shostakovich, Sergei Prokofiev, Sofia Gubaidulina, and Sviatoslav Richter; and on a broad range of topics in twentieth-century music